A survey of the factors influencing the resistance of the employees of university libraries to technological changes: Study of libraries of Tehran University. Issue 8 (14th November 2017) - Nakhoda, Maryam; Tajik, Samaneh
Abstract : Purpose: The purpose of this paper is to study the factors influencing the resistance of the employees of Tehran University libraries to technological changes. Through achieving this aim, it attempts to provide a suitable understanding of these factors for the managers so that they would be able to reduce the resistance to change among the employees of university libraries. Design/methodology/approach: This study is a descriptive survey in its data collection method. Based on the review of the literature, a questionnaire on resistance to technological changes was devised (Cronbach's α coefficient being 93 percent). The questionnaire was distributed among 128 of the employees in the technology section of Tehran University libraries, and the achieved data were analyzed using an SPSS and PLS. Findings: The findings achieved through a confirmatory factor analysis showed 11 elements of ambiguity, threat of the current situation, habit, lack of interest, the need for relearning, unsuitable understanding, inefficient rewarding system, emotional reactions, lack of interest understanding, inflexibility of the beliefs and feeling of being a veteran in the organization, which influence the resistance of the employees of the university libraries, among them the inefficient rewarding system ranks first and the unsuitable understanding ranks last. Originality/value: In this research, an attempt is made to identify the resistance to technological changes shown by the employees of Tehran University libraries, which can be a guide for library managers to improve the changing process in their libraries. Influencing factors of resistance to change which had been identified by other research works were examined here regarding the circumstances of Tehran University Libraries.